The diffusion of digital technology among Millennials and Gen X in the South African Aviation Industry - Kgodane, Kabelo (University of the Witwatersrand, Johannesburg, 2023)
As digital technology continues to shape the aviation industry, it remains unclear how millennials and gen x help or hinder the diffusion of digital technology in the workplace to improve usage and shape the passenger digital technologies in the industry. This study examines the impact of millennials and gen x on the diffusion of digital technology in the South African Aviation Industry. A qualitative approach was adopted, and 12 participants were purposively selected and interviewed (with an equal representation of millennials and gen x). The participants were asked questions relating to their role as contributors to passenger digital technologies in the industry and as passengers (consumers of passenger digital technologies). The data was analysed thematically using an inductive and deductive approach to capture the rich responses. Rogers’ Diffusion of Innovations theory underpinned this study and also informed the interviews and analysis of the data. The findings were in-depth insights that showed the two generational cohorts’ meaningful contributions in the workplace. Overall, the study found that millennials and gen x share similarities in their attitudes about the advantages and concerns of using passenger digital technologies in the workplace and showed differences in the challenges and disadvantages of using the technologies as passengers. Age, the social system, communication channels, and the role of time were found to play a big role in the diffusion process. The theoretical framework was useful in structuring the interviews and analysing the data collected using themes that emerged from the data and the framework. The findings indicated that the two generational cohorts belong to two important adopter category groups, which help the workplace diffusion process. This study contributes valuable insights that enrich the existing body of knowledge in the South African Aviation Industry. There are not many contributions related to the diffusion and usage of digital technology in the South African Aviation industry and in those that exist researchers use quantitative approaches to collect data. This study however illustrated the importance of using qualitative methodology in analysing the insights from the participants which provided a deeper
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital Technology; Passenger Digital Technology; Diffusion of Innovation; South African Air Transport Industry; Generation X; Millennials; UCTD; SDG-9: Industry, innovation and infrastructure